1996
DOI: 10.1177/154193129604002315
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Caffeine and Gender on Vigilance and Marksmanship

Abstract: Sentry duty performance requires both rifle marksmanship accuracy and sufficient attention to detect the infrequent appearance of targets. Research has shown that marksmanship accuracy is in part a function of arm-hand steadiness, that arm-hand steadiness may be better in women than men, and that in men 200 mg caffeine heightens alertness and attenuates vigilance decrements. Study objectives were: (a) evaluate gender differences in speed of target detection and rifle firing accuracy during three hours of simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 6 publications
1
26
1
Order By: Relevance
“…Johnson and Merullo (1996) found that for 3-hour test sessions, target detection response time deteriorated with time on sentry duty and that vigilance decrements were attenuated by 200 mg of caffeine. For men, marksmanship accuracy was constant over time; for women, marksmanship accuracy deteriorated after 1.5 hours.…”
Section: Sleep Deprivation Circadian Rhythm and Marksmanshipmentioning
confidence: 95%
“…Johnson and Merullo (1996) found that for 3-hour test sessions, target detection response time deteriorated with time on sentry duty and that vigilance decrements were attenuated by 200 mg of caffeine. For men, marksmanship accuracy was constant over time; for women, marksmanship accuracy deteriorated after 1.5 hours.…”
Section: Sleep Deprivation Circadian Rhythm and Marksmanshipmentioning
confidence: 95%
“…Most of the studies involving shooting performance by Johnson and McMenemy (1989), Johnson (1995), and Johnson and Merullo (1996) at the U.S. Army Research Institute of Environmental Medicine have used the Weaponeer system. Wolf (1989) however, describes a program of instruction for basic rifle marksmanship training and suggests ways of maintaining unit effectiveness in marksmanship after formal training.…”
Section: Simulators and Marksmanship Trainingmentioning
confidence: 99%
“…Numerous studies have been performed with the Weaponeer as a shooting research platform (Schendel, 1982;Abbott, 1991;Johnson & Merullo, 1996, Johnson & McMenemy, 1989, although some studies have employed the use of the MACS (Abbott, 1991) and the EST (Hagman, 1998).…”
Section: Simulated Fire and Live Fire Performancementioning
confidence: 99%
“…In addition, even in rested warfighters that are required to maintain alertness for long periods of time, key aspects of cognitive performance, in particular vigilance, significantly deteriorate (Johnson, 1991;Johnson and Merullo, 1996). One strategy that can be employed to mitigate, in part, such decrements in cognitive performance is the administration of the food component/drug caffeine.…”
Section: Introductionmentioning
confidence: 99%